KARAKTERISTIK DAN PERSEPSI KENYAMANAN WISATAWAN MANCANEGARA DI PANTAI KUTA BALI - Juniawan, I Made; Oka Karini, Ni Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
Based the bad environment of Kuta, such as narrow roads, traffic jam, and less of parking area, also less of security sector that happens to prevent crime like a terrorism, murder, or theft. Therefore, this research done to know how the characteristics of foreign tourist who come to Kuta, and whether the tourists still feel comfortable, with the negative impact that arising from tourism activities at Kuta. The method of research using quantitative and qualitative descriptive, with Purposive Sampling as sampling technique, also Sampling Quota and Incidental Sampling as technique taking a sample. By utilize observation, questioners, and document study as method collecting of data. Characteristics of foreign tourists who come to Kuta beach dominated by male tourists with age 21-25 years. Almost of tourists who visiting Kuta has the occupation as student or college. Where, 33% of tourists coming from Australia. Base on final systematic calculation, obtain the final result 3.66, which entered into good category. Therefore, if make a connecting the final result with the Table Interval Comfort Level Criteria, get the conclusion that perception the comfort of foreign tourists at Kuta beach Bali entered into comfortable category. There are factors that obtain greatest value that is Natural resources/climate, Relationship with local people, Beauty, Cleanness, and Relationship between the tourists.
Keywords: Characteristic, Comfort, Foreign tourist, Kuta Beach Bali